Merajut Kembali Komunitas Damai: Studi Landasan Biblis Dan Teologis Resolusi Konflik - Agus Supratikno (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2019)
"REINFORCING PEACEFUL COMMUNITIES": The Study of Biblical and Theological Foundations for Conflict Resolution. Studi  Landasan Biblis dan Teologis Untuk Membangun Komunitas Damai. Plurality which is considered as a nation's wealth, it also turns out to be the cause of the emergence of conflicts with nuances of ethnicity, race and religion. Unfortunately political elites often politicize issues based on ethnic and religious sentiments to gain power. They did not consider the serious effects that were caused as a result of the politicization of ethnic and religious issues. Horizontal conflicts with nuances of religion and ethnicity that have occurred in various regions in Indonesia, such as in Ambon, Poso, Kalimatan, are more often triggered by the politicization of religious and ethnic issues or initially the conflict is not caused by ethnic or religious problems, but often the conflict brought to the realm of religion so as to make the conflict increasingly enlarged and inevitable. This writing is an effort to explore the biblical and theological foundation for an effort to build a peaceful community post the conflict. This study uses hermeneutic studies and the library research methods by utilizing library resources both books and journals related to conflict resolution.  MERAJUT KEMBALI KOMUNITAS DAMAI”: Studi  Landasan Biblis dan Teologis untuk Resolusi Konflik. Pluralitas yang dianggap sebagai suatu kekayaan bangsa, ternyata juga bisa menjadi penyebab munculnya konflik bernuansa suku, ras dan agama. Sayangnya para elite politik justru sering mempolitisasi isu-isu berdasarkan sentimen suku dan agama untuk meraih kekuasaan. Mereka  tidak mempertimbangkan dampak serius yang ditimbulkan sebagai akibat politisasi isu suku dan agama. Konflik-konflik horizontal bernuansa agama dan suku yang pernah terjadi di berbagai daerah di Indonesia, seperti di Ambon, Poso, Kalimatan, lebih sering dipicu oleh adanya politisasi terhadap isu agama dan suku. Pada awalnya konflik tersebut bukanlah disebabkan oleh masalah agama, tetapi seringkali konflik tersebut dibawa ke ranah agama sehingga menjadikan konflik semakin membesar dan tak terelakkan.Tulisan ini adalah sebuah upaya menggali landasan biblis dan teologis bagi suatu upaya merajut kembali komunitas damai pasca konflik.  Penelitian ini menggunakan metode perpaduan antara studi hermeneutik dan literatur dengan memanfaatkan sumber-sumber pustaka baik buku maupun jurnal yang berkaitan dengan topik yang dibahas.